2021
DOI: 10.1002/ejoc.202100053
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Imidazoles from Fatty 1,2‐Diketones

Abstract: Unsaturated vegetable oils and their corresponding fatty acid derivatives constitute interesting renewable platforms for the preparation of heterocycles, notably through the formation of oxygenated intermediates. In this work, fatty imidazoles were prepared from the corresponding 1,2‐diketones through Debus‐Radziszewski reaction. The reaction was optimized under microwave irradiation using a 1,2‐diketone derived from methyl oleate and ammonium acetate as a nitrogen source. Using benzaldehyde as a model substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 90 publications
3
4
0
Order By: Relevance
“…The reduction of butane-2,3-diimine concentration in the acid-catalyzed HTL was due to the cycloaddition of the carbonyl carbon of formaldehyde toward the −NH 2 groups of butane-2,3-diimine, yielding 4,5-dimethyl-imidazole in biocrude. 47 This result showed that the cycloaddition favored acidic conditions, agreeing with its higher frequency factor and lower activation energy for r 39 under more acidic feedstock pH (see Table 1). Moreover, Table S33 shows an increased concentration of 4,5dimethyl-imidazole at higher temperatures, highlighting the endothermic (r 39 ; ΔH = 66.7 kJ/mol) cycloaddition as the rate-controlling step.…”
Section: Scenariosupporting
confidence: 70%
See 1 more Smart Citation
“…The reduction of butane-2,3-diimine concentration in the acid-catalyzed HTL was due to the cycloaddition of the carbonyl carbon of formaldehyde toward the −NH 2 groups of butane-2,3-diimine, yielding 4,5-dimethyl-imidazole in biocrude. 47 This result showed that the cycloaddition favored acidic conditions, agreeing with its higher frequency factor and lower activation energy for r 39 under more acidic feedstock pH (see Table 1). Moreover, Table S33 shows an increased concentration of 4,5dimethyl-imidazole at higher temperatures, highlighting the endothermic (r 39 ; ΔH = 66.7 kJ/mol) cycloaddition as the rate-controlling step.…”
Section: Scenariosupporting
confidence: 70%
“…Given that the HTL of acidic feedstocks in scenarios 2a and 2b producing 4,5dimethyl-imidazole and 1,3,4,5-tetramethyl-2,3-dihydro-1Himidazole employed phosphoric acid as the acidifying agent to pH 2, this result demonstrated that the Debus− Radziszewski reaction involving biacetyl was only catalyzed by a high concentration of homogeneous strong acid catalysts, consistent with the literature. 40,47 Scenario 2e (i.e., HTL of pyruvaldehyde, glycine, and fumaric acid mixtures) validated the precipitation of (Z)-1,13diimino-2,5,9,12,13,14,14a,14b-octahydro-1H,7H-azepino-[1′,2′:3,4]-imidazo[1,5-a]azocine-3,11-dicarbonitrile (DOAIAD) in hydrochar from the HTL of the acidic feedstock mixture. Figure 6E shows a decreasing concentration of fumaric acid (i.e., the oxidation product of furfural, r 46 ) with reaction time under acid-catalyzed and alkaline-catalyzed processes due to the amidation and dehydration into fumaronitrile.…”
Section: Scenariomentioning
confidence: 99%
“…The Debus–Radziszewski reaction ( R 22) was responsible for the imidazole formation. This reaction included the formation of a diamine intermediate from monosaccharide-derived α-dicarbonyl and 1° amine before condensing with an aldehyde forming an imidazole . The formation of pyrazoles followed the Knorr-type reaction ( R 20) involving a hydrazine and a 1,3-dicarbonyl .…”
Section: Resultsmentioning
confidence: 99%
“…This reaction included the formation of a diamine intermediate from monosaccharidederived α-dicarbonyl and 1°amine before condensing with an aldehyde forming an imidazole. 88 The formation of pyrazoles followed the Knorr-type reaction (R20) involving a hydrazine and a 1,3-dicarbonyl. 89 The formation of dialkylhydrazines (R39) occurred through the Raschig mechanism (i.e., direct nucleophilic attack by the 2°amine) that required a reaction between dialkylamine and chloramine, generated in situ by the reaction of ammonia with potassium hypochlorite.…”
Section: Strong Basic Sitesmentioning
confidence: 99%
“…Methyl erythro - and threo -9,10-dihydroxystearates ( erythro / threo -9,10-bisOH-18:Me) as well as methyl cis –9,10–epoxystearate ( cis -9,10-epoxy-18:Me) were prepared according to published procedures (Scheme S1 in the Supporting Information ) [41] , [42] . The synthesis of 9-, 10- and 11–hydroxystearic acids was based on a modular method starting from corresponding ω -hydroxyalkanoic acids (Schemes S2–S4).…”
Section: Resultsmentioning
confidence: 99%